The Effect of the Barrierhops Training Method on the Volleyball Smash at SMA Negeri 5 Lebong - Desmi Triyanti (Penerbit Jurnal Indonesia, 2021)
The purpose of this study was to determine the ability to jump on the smash of male students in volleyball extracurricular at SMAN 5 Lebong. The type of research used in this research is quasi-experimental. With a population of 30 and a sample of 30 students, the sampling technique used was total sampling. Data analysis technique using t test. As for the research results obtained by the Hypothesis Test tcount 15.15 in the rejection area Ho t table 2.048 in the rejection area Ho then Ha can be accepted. With a calculation percentage of 53% it can be concluded that there is an effect of Barrierhops training on the smash of male students in extracurricular volleyball at SMAN 5 Lebong. Based on the results of the research and discussion that have been described in the previous chapter, it can be concluded that the proposed hypothesis is accepted, namely that there is an effect of barrier hops training on the jumping ability of the male students in extracurricular volleyball at SMAN 5 Lebong. Plyometric training on the ability to jump smash, it can be concluded that there is a significant effect between the barrier hops exercise on the jumping ability of the male students in extracurricular volleyball at SMAN 5 Lebong.